Extracorporeal life support for immune reconstitution inflammatory syndrome in HIV patients with Pneumocystis jirovecii pneumonia - Ramanathan, Kollengode (J Artif Organs, 2018)
Patients with immunosuppression from human immunodeficiency virus (HIV) have been traditionally considered poor candidates for extracorporeal membrane oxygenation (ECMO) because of high in-hospital mortality and poor long-term survival. Highly active antiretroviral therapy (HAART) has improved survival rates in compliant HIV patients and reversible severe respiratory failure may warrant ECMO in this group. Immune reconstitution inflammatory syndrome (IRIS) involves excessive inflammatory response to a pathogen with paradoxical clinical deterioration following HAART initiation and may present as severe respiratory failure. Patients with IRIS supported on ECMO have been infrequently reported in literature. We report two HIV-positive patients who developed acute respiratory distress syndrome from IRIS necessitating successful veno-venous ECMO as salvage therapy.